Bridging NEET Status and Employability Through Digital Literacy: Implications for TVET Policies in the Digital Age - Bahçekapılı, Ekrem; Neagu, Gabriela; Berigel, Muhammet (Calitatea Vieții, 2025)
In the digital age, the employability, quality of life and social inclusion of young people, particularly those classified as NEET (Not in Education, Employment, or Training), is increasingly linked to their digital literacy. This study examines the relationship between digital skills and NEET rates across European Union countries, emphasizing the role of Technical and Vocational Education and Training (TVET) policies in addressing digital exclusion. By analyzing Eurostat data for 2023, the research investigates disparities in digital competencies among NEET populations based on gender, age, and regional differences. The primary aim is to assess how digital skills impact employability and to propose policy recommendations for integrating digital literacy into TVET curricula. To achieve this, the study employs hierarchical clustering analysis to categorize EU countries based on their NEET rates and digital skills distribution. The dataset comprises Eurostat statistics from 32 European countries. The key variables analyzed include employment status and digital skill levels categorized as high, basic, low, or none. The clustering results highlight critical gaps in digital education and underscore the need for tailored TVET policies that equip NEET youth with relevant digital competencies. This study provides evidence-based policy recommendations to bridge the digital divide, enhance labor market integration, and align vocational training with the evolving demands of the digital economy. The findings contribute to the broader discourse on digital inclusion and workforce preparedness in the modern labor market.